Inflation Expectations in the U.S. : Linking Markets, Households, and Businesses - Williams, Peter (IMF Working Papers; Working Paper ;, 2020)
Inflation has been below the Federal Reserve's target for much of the past 20 years, creating worries that inflation may be deanchoring from the FOMC's target. This paper uses a factor model that incorporates information from professional forecasters, household and business surveys, and the market for Treasury inflation protected securities (TIPS) to estimate long-run inflation expectations. These have fallen notably in the past few years (to roughly 1.9 percent for CPI inflation, well below the FOMC's target). It appears that, even before the covid recession, the private sector viewed the economy as likely to suffer from persistent headwinds to inflation.